Analisis Gender dan Gaya Kepemimpinan pada Industri Perhotelan di Bali - Tettie Setiyarti; Ni Made Dewi Lestari (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2020)
More than 200 million people work in the tourism sector, and women represent 55.5% of this amount. However, the level of participation of Balinese women in the tourism sector is still fairly low. This paper aims to study the roles and positions of women in various management positions in the hotel industry located in Bali. The type of data used consisted of qualitative data, collected through semi-structured interviews with 15 male managers and 15 female managers working in the 4-star hotels, whom were selected using convenience sampling techniques, while the analysis techniques used is thematic analysis. The results of this study indicate that men and women have the same career opportunities in the hospitality industry in Bali. Barriers that have been echoed according to respondents are internal in nature. Because both men and women have the same abilities needed to get the job done, however the research found that women are more flexible in their role as leaders by providing trust and establishing good communication with colleagues or subordinates.